(untitled) (MAUSAM, 1984)
In an attempt to predict wet/dry spell and weather cycle, Markov chain model was fitted to the daily rainfall data (1958 to 1980) of Chandigarh. Conditional probabilities for occurrence of wet day preceded by wet/dry day were calculated and the expected frequencies of wet and dry spell and the weather cycle have been worked out with the help of the model. The study on the basis of X2 test has revealed the expected frequencies to fall in agreement with the observed ones.